(2x-3)(2x-3)=81

Simple and best practice solution for (2x-3)(2x-3)=81 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-3)(2x-3)=81 equation:


Simplifying
(2x + -3)(2x + -3) = 81

Reorder the terms:
(-3 + 2x)(2x + -3) = 81

Reorder the terms:
(-3 + 2x)(-3 + 2x) = 81

Multiply (-3 + 2x) * (-3 + 2x)
(-3(-3 + 2x) + 2x * (-3 + 2x)) = 81
((-3 * -3 + 2x * -3) + 2x * (-3 + 2x)) = 81
((9 + -6x) + 2x * (-3 + 2x)) = 81
(9 + -6x + (-3 * 2x + 2x * 2x)) = 81
(9 + -6x + (-6x + 4x2)) = 81

Combine like terms: -6x + -6x = -12x
(9 + -12x + 4x2) = 81

Solving
9 + -12x + 4x2 = 81

Solving for variable 'x'.

Reorder the terms:
9 + -81 + -12x + 4x2 = 81 + -81

Combine like terms: 9 + -81 = -72
-72 + -12x + 4x2 = 81 + -81

Combine like terms: 81 + -81 = 0
-72 + -12x + 4x2 = 0

Factor out the Greatest Common Factor (GCF), '4'.
4(-18 + -3x + x2) = 0

Factor a trinomial.
4((-3 + -1x)(6 + -1x)) = 0

Ignore the factor 4.

Subproblem 1

Set the factor '(-3 + -1x)' equal to zero and attempt to solve: Simplifying -3 + -1x = 0 Solving -3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 0 + 3 -1x = 0 + 3 Combine like terms: 0 + 3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3

Subproblem 2

Set the factor '(6 + -1x)' equal to zero and attempt to solve: Simplifying 6 + -1x = 0 Solving 6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 0 + -6 -1x = 0 + -6 Combine like terms: 0 + -6 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6

Solution

x = {-3, 6}

See similar equations:

| 16-3p=2/3pt5 | | Sec^2x+2tanx=0 | | 1-2-7= | | Y=49(0.27)x | | (x-2)(Inx-3)=0 | | (x-2)(lnx-3)=0 | | 11=w-8/15 | | 14x^2+1=12x | | 5X-8=3(x-10) | | 16x+5=x-11 | | (1.25x/4)^16 | | f(x)=(1.25x/4)^16 | | Simplify(2/4-2/3)x11/5 | | 88-d=52+4d | | 8=-14(1)+b | | 1.03p-4=(-2.15p)+8.72 | | 2(3x+-10)=25 | | 1-2x/9=6/7 | | -160=-n+4(-7-8n) | | 3(x+1)+2(x-1)=21 | | 4(x+5)+3=9x+4(x+3) | | (9x-6)(5x+9)= | | 5(7+x)=12+5+5x | | (x+3)+51=90 | | 4x=254 | | 9x-6+2x-x+7=16x+8-x-3 | | 4x(x-7)=16 | | 6x-3d+2d-6=4x | | 5=w/5.5 | | 3x+210=360 | | 9x(x+9)=135 | | 6x+5=x-11 |

Equations solver categories